A Study on Development and Characterization of Chemicals for Cancer Control: Exploring new strategies for cancer therapy (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Cancer is still one of the major causes of mortality in both developing and developed countries. At present, in spite of intensive interventions, a large number of patients suffer from poor prognosis. Therefore, the effort for finding new anticancer agents with better efficacy and lesser side effects has been continued. This review was focused on the Natural compounds targeting cancer stem cells, Cancer-producing chemical compounds and Compound chemical analysis and target prediction.